MAKNA AL SIYADAH DAN AL TABIIYAH (STUDI TAFSIR MUQARAN) - Lailatul Mas’udah (Institut Keislaman Abdullah Faqih Gresik, 2020)
Humans are created in groups according to their respective communities and interact through various media and languages, and humans cannot live alone because of that humans are called social beings. In carrying out activities as social beings, humans have rules and norms that apply to live a life together that have been agreed upon in order to create harmony and balance between people. As a first step towards harmonizing and shaping norms and rules in social society, they make an agreement to choose one of them as the controlling holder who is called the leader. Holder of control which is then called sovereignty. Not all sovereignty is in the hands of leaders, but some countries make the people in control of the sovereignty of the social society. The understanding of sovereignty and populism has been discussed in the Koran with various meanings, functions and kinds. In this understanding, he tries to explore the meaning of sovereignty framed in a pair of synonymous lafad, namely lafad al Siyadah and al Tabiiyah. The research method used in this research is qualitative with the Ulumul quran approach and interpretation with the Maudhui concept or library research theme. Through this method and approach, it is hoped that it will be able to reveal the meaning of al Siyadah and al Tabiiyah lafad and the relationship between the two lafad from various aspects that have been listed in the verses of al-Qura.Keyword: al Quran, al Sayyid, al Tabi ', sovereignty